The relationship of tooth shade and skin tone and its influence on smile attractiveness in native South Indians: A web-based cross sectional survey - Hrudi Sundar Sahoo; Aishwarya Balasubramanian (Journal of Oral Biology and Craniofacial Research)
Objectives: This study aimed to investigate the influence of tooth shade and skin tone on smile attractiveness among native South Indians. The primary research question was whether there is a significant relationship between these variables and perceived smile attractiveness. Materials and methods: A web-based cross-sectional survey was conducted with approval from the Institutional Review Board of (Thai Moogambigai Dental College and Hospital, Chennai). Standardized smile photographs of two South Indian models (one male and one female) were digitally modified to display four different tooth shades and four different skin tones, resulting in 32 images. These images were incorporated into a Google Form along with a questionnaire and a Visual Analog Scale (VAS) for attractiveness rating. The survey was distributed to 1200 participants, including both dental professionals and the general population, with 1000 valid responses recorded. Statistical analysis was performed using IBM SPSS Statistics, employing parametric tests to evaluate the data. Results: The study found that lighter tooth shades were consistently rated higher in attractiveness for both genders. Lighter tooth shades such as FS1T1 and FS2T1 scored means of 6.88 and 7.27 respectively for females, while darker shades like FS1T4 scored lower with a mean of 4.95. Similarly, males showed a preference for lighter tooth shades with MS1T1 and MS2T1 scoring means of 5.57 and 5.78 respectively compared to darker shades like MS1T4 with a mean of 3.63. Significant differences were noted across age groups and genders, with younger participants and females showing a stronger preference for lighter tooth shades. Conclusions: The study concludes that both tooth shade and skin tone significantly influence smile attractiveness, with a clear preference for lighter tooth shades among the surveyed population. These findings suggest the importance of considering these factors in aesthetic dental treatments to enhance patient satisfaction and achieve optimal results. Clinical relevance: The results underscore the necessity for dental practitioners to take into account both tooth shade and skin tone when planning aesthetic dental treatments. This approach will help in achieving a more harmonious and natural appearance, ultimately improving patient satisfaction with the treatment outcomes. Future research should continue to explore the cultural and individual factors that contribute to these preferences in dental aesthetics.